2009
DOI: 10.1295/polymj.pj2009077
|View full text |Cite
|
Sign up to set email alerts
|

Thickness Anomalies in Supported Polystyrene Films with Thicknesses Comparable to the Radius of Gyration

Abstract: We report on X-ray reflectivity of ultrathin polystyrene films with thickness h, which is comparable to the radius of gyration R g . Tiny jumps in thickness, accompanying an increase in surface roughness and decrease in electron density, are reproductively observed at around 80 C and 92 C only with increasing temperature. For films thinner than R g , the jump at 92 C disappears. However, films of 2R g thick, the jump at 80 C is hardly observed with a faint trace in slope at this temperature. For much thicker f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
(26 reference statements)
1
6
1
Order By: Relevance
“…The in-plane heterogeneous periodicity of surface undulation gives diffuse scattering normal to the q z direction in reciprocal space; therefore, the broad peak observed in the q z scan profiles might originate from the diffuse scattering component superimposed on the specular reflection along the q z direction. Another possibility of the emergence of the broad peak is the presence of a periodic layered structure normal to the PS surface; however, this is not probable because the periodic layered structure normal to the sample surface would exhibit a periodic interference fringe pattern in the XR profiles, as reported in previous studies [1,4,7,20,23,24]. We observed only one peak at q z = 0.04Å −1 in the XR profiles.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The in-plane heterogeneous periodicity of surface undulation gives diffuse scattering normal to the q z direction in reciprocal space; therefore, the broad peak observed in the q z scan profiles might originate from the diffuse scattering component superimposed on the specular reflection along the q z direction. Another possibility of the emergence of the broad peak is the presence of a periodic layered structure normal to the PS surface; however, this is not probable because the periodic layered structure normal to the sample surface would exhibit a periodic interference fringe pattern in the XR profiles, as reported in previous studies [1,4,7,20,23,24]. We observed only one peak at q z = 0.04Å −1 in the XR profiles.…”
Section: Resultssupporting
confidence: 62%
“…After nonlinear least-squares refinement, the electron density and surface roughness of the PS samples were converged to 0.33 e/Å 3 and 11.7Å, respectively. The electron density of the PS sample is almost comparable to that of the PS thin films at room temperature [20] and the surface roughness is sufficiently small to evaluate the surface structure by XR measurements. Thus, the XR analysis revealed that the PS surface fabricated by the aforementioned method exhibits atomic-scale flatness.…”
Section: Methodsmentioning
confidence: 93%
“…On the other hand, very little is known or understood about the nature of dispersion of nanoparticles in thin polymer films [5][6][7]9,10,12 . This is a bit surprising since, a vast amount of research has been devoted to understanding of structure and properties of thin polymer films, especially those related to the perturbation of chain conformation [17][18][19][20][21] and glass transition due to confinement [5][6][7][8]11,[22][23][24][25] . Although there is significant progress in understanding the chain conformation with confinement, some conflicting reports still exist [18][19][20]26,27 .…”
mentioning
confidence: 99%
“…This is a bit surprising since, a vast amount of research has been devoted to understanding of structure and properties of thin polymer films, especially those related to the perturbation of chain conformation [17][18][19][20][21] and glass transition due to confinement [5][6][7][8]11,[22][23][24][25] . Although there is significant progress in understanding the chain conformation with confinement, some conflicting reports still exist [18][19][20]26,27 . Similarly, in the case of glass transition of thin polymer films, contradictory reports on finite size effects on T g in polymer thin films have emerged [5][6][7][8][22][23][24] .…”
mentioning
confidence: 99%
“…The details of the analysis have been previously described. 32,33 RESULTS Figure 1 illustrates the temperature dependence of the normalized thicknesses that were obtained at heating rates of 0.14 1C Figure 1 are the fitted curves obtained by assuming the 'tanh' profile approximation: 4…”
Section: Methodsmentioning
confidence: 99%